RETROPHARYNGEAL ABSCESS: A CLINICAL STUDY - Ghani, Rehman; Nabi, Ghulam; Shehzad, Khawar (Journal of Ayub Medical College Abbottabad, 1998)
Retropharyngeal abscesses are more common in children than the adult population. This is a potentially lethal infection in the Paediatric population under the age of five years. Abscesses in this group are secondary to upper respiratory tract infection. In the adult group they are usually secondary to trauma, foreign bodies or as a complication of dental infections. We have treated 12 cases of Retropharyngeal Abscesses between 1990 to 1998 in our department. Factors such as age, sex, aetiology, presenting signs & symptoms, methods of diagnosis, treatment and complications are reviewed. A lateral neck film showing widening of the prevertebral space was the most diagnostic tool. Ten cases required surgical drainage. The other two were completely cured with parenteral broad spectrum Antibiotics. The most commonly isolated pathogen was streptococcus pyogenes. There were no deaths and only one recurrence required repeated surgical drainage.